Ginsenoside Rb1 Improves Metabolic Disorder in High-Fat Diet-Induced Obese Mice Associated With Modulation of Gut Microbiota - Zou, Hong; Zhang, Man; Zhu, Xiaoting; Zhu, Liyan; Chen, Shuo; Luo, Mingjing; Xie, Qinglian; Chen, Yue; Zhang, Kangxi; Bu, Qingyun; Wei, Yuchen; Ye, Tao; et al. (Frontiers in Microbiology, 2022)
Gut microbiota plays an important role in metabolic homeostasis. Previous studies demonstrated that ginsenoside Rb1 might improve obesity-induced metabolic disorders through regulating glucose and lipid metabolism in the liver and adipose tissues. Due to low bioavailability and enrichment in the intestinal tract of Rb1, we hypothesized that modulation of the gut microbiota might account for its pharmacological effects as well. Here, we show that oral administration of Rb1 significantly decreased serum LDL-c, TG, insulin, and insulin resistance index (HOMA-IR) in mice with a high-fat diet (HFD). Dynamic profiling of the gut microbiota showed that this metabolic improvement was accompanied by restoring of relative abundance of some key bacterial genera. In addition, the free fatty acids profiles in feces were significantly different between the HFD-fed mice with or without Rb1. The content of eight long-chain fatty acids (LCFAs) was significantly increased in mice with Rb1, which was positively correlated with the increase of Akkermansia and Parasuttereller, and negatively correlated with the decrease of Oscillibacter and Intestinimonas. Among these eight increased LCFAs, eicosapentaenoic acid (EPA), octadecenoic acids, and myristic acid were positively correlated with metabolic improvement. Furthermore, the colonic expression of the free fatty acid receptors 4 (Ffar4) gene was significantly upregulated after Rb1 treatment, in response to a notable increase of LCFA in feces. These findings suggested that Rb1 likely modulated the gut microbiota and intestinal free fatty acids profiles, which should be beneficial for the improvement of metabolic disorders in HFD-fed mice. This study provides a novel mechanism of Rb1 for the treatment of metabolic disorders induced by obesity, which may provide a therapeutic avenue for the development of new nutraceutical-based remedies for treating metabolic diseases, such as hyperlipidemia, insulin resistance, and type 2 diabetes.